The influence of maternal HIV status on mortality in children under the age of five years - Makala, Lukuni (University of Cape Town, 2021)
Child mortality can be used to measure the level of social development as well as the health status of children (Hill 1991). By world regions, sub-Saharan Africa maintains the highest rates of under-five mortality. Current under-five mortality is estimated at 76 deaths per 1,000 live births (Hug, Sharrow, Zhong et al. 2018). In Zambia, under-five mortality reached a peak of 197 in 1996 and is currently estimated at 60 (Hug, Sharrow, Zhong et al. 2018). On the world health agenda, reducing child mortality has been made a priority, especially for low income countries that remain the most affected. Among the targets of the Sustainable Development Goals (SDGs) is reduction of neonatal mortality to at least 12 deaths per 1,000 live births and under-five mortality to 25 deaths by 2030 (United Nations 2015). HIV/AIDS is one of the leading causes of mortality in Zambia and has contributed to the slow decline of under-five mortality (Garenne and Gakusi 2006). Children under the age of five years get infected with HIV mainly through vertical transmission (Fishel, Ren, Barrère et al. 2014). In the absence of treatment, vertical transmission of HIV is high and can range between 15 and 45 per cent, reducing below 5 per cent with effective interventions (Barral, Oliveira, Lobato et al. 2014). Despite vertical transmission being the main pathway through which children get infected with HIV, little research has been done to determine the significance of maternal HIV status on under-five mortality in Zambia. The aim of the study was, therefore, to determine the extent to which mortality of children with HIV-positive mothers differs from that of children with HIV-negative mothers. The Zambia Demographic and Health Survey (ZDHS) data for 2007 and 2014 which contain HIV serotesting data were used. Survival analysis using Poisson regression was used to model the influence of maternal HIV status taking into account confounding factors. The results of the study indicate that maternal HIV status was significantly associated with child mortality in both survey periods but by 2013/14 the influence of maternal HIV status had reduced and was insignificant for children born within one year of the 2013/14 survey. The reduction in the risk of dying between the inter-survey period may be as a result of increased coverage of prevention of mother-to-child transmission (PMTCT) and antiretroviral therapy (ART) services over the years. In order to reach universal coverage, there is need for increased provision of PMTCT and ART treatments and support for HIV strategies such as the 90 90 90 target.